2009
DOI: 10.1038/nature07811
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IFRD1 as a modifier gene for cystic fibrosis lung disease

Abstract: Lung disease is the major cause of morbidity and mortality in cystic fibrosis (CF), an autosomal recessive disease caused by mutations in CFTR. In CF, chronic infection and dysregulated neutrophilic inflammation lead to progressive airway destruction. The severity of CF lung disease has significant heritability, independent of CFTR genotype1. To identify genetic modifiers, we performed a genome-wide single nucleotide polymorphism (SNP) scan in one cohort of CF patients, replicating top candidates in an indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
113
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 32 publications
2
113
0
2
Order By: Relevance
“…STAT3, IL1B and IFNGR1 as CF modifiers H Labenski et al carries the causative variant, followed by re-sequencing of contrasting haplotypes to describe the sequence variants for which cases and control differ comprehensively by the base (IFNGR1). Although modern high-throughput technology allows for genomewide scans using SNP, 43,44 microsatellites 45 or in-depth investigation of candidate genes with multiple SNPs, 27 reports of modifying variants that have been systematically mapped and functionally validated by means of modifier-genotype/patient's-phenotype correlation are still the exception in the CF modifier field. In the light of this, we admit that the direct correlation between the length of the intronic microsatellite STAT3Sat and STAT3 expression levels among F508del-CFTR homozygous patients was an unexpected finding by serendipity as STAT3Sat was purely genotyped to capture inherited variants of the candidate gene.…”
Section: Dbe Agarosementioning
confidence: 99%
“…STAT3, IL1B and IFNGR1 as CF modifiers H Labenski et al carries the causative variant, followed by re-sequencing of contrasting haplotypes to describe the sequence variants for which cases and control differ comprehensively by the base (IFNGR1). Although modern high-throughput technology allows for genomewide scans using SNP, 43,44 microsatellites 45 or in-depth investigation of candidate genes with multiple SNPs, 27 reports of modifying variants that have been systematically mapped and functionally validated by means of modifier-genotype/patient's-phenotype correlation are still the exception in the CF modifier field. In the light of this, we admit that the direct correlation between the length of the intronic microsatellite STAT3Sat and STAT3 expression levels among F508del-CFTR homozygous patients was an unexpected finding by serendipity as STAT3Sat was purely genotyped to capture inherited variants of the candidate gene.…”
Section: Dbe Agarosementioning
confidence: 99%
“…However, many modifiers identified in single, small populations by candidate gene approaches could not be reproduced and/or lacked functional analyses of the investigated variants. Among the best established CF lung disease modifiers are mannose binding lectin, 23 interferon-related developmental regulator 1, 5 and transforming growth factor-beta1, with the risk genotype of the latter having an odds ratio of 2.2 in association with severe lung disease. 4 As CF modifiers identified so far could not fully explain the phenotypic variability observed in CF, whole-genome association studies were initiated in order to detect yet unknown pathways associated with CF severity.…”
Section: Discussionmentioning
confidence: 99%
“…2 The phenotypic expression of CF shows a broad variability, even among patients carrying the same CFTR genotype. Besides environmental and other factors, variability is due to modifier genes 3 that influence the immune response in CF [4][5][6] or modify ion flux at the apical membrane. 7 In addition, it has been proposed that members of the so-called CFTR-interactome influence CF clinics.…”
Section: Introductionmentioning
confidence: 99%
“…A 3´UTR sequence variation, that increased pulmonary EDNRA expression and airway inflammation, was significantly associated with decreased pulmonary function in ΔF508 homozygous CF patients [Darrah, et al, 2009]. Sequence variations in other genes with roles in inflammation/immune function, such as TGFB1 [Drumm, et al, 2005], IL8 [Hillian, et al, 2008] and IFRD1 [Gu, et al, 2009], have also been identified as CF modifier genes. CF modifier genes are also likely to play a role in the development of CFTR-related diseases in the presence of single allele CFTR mutations, such as the c.-34C>T mutation described here.…”
Section: Discussionmentioning
confidence: 99%